DENTAL HEALTH EDUCATION INFLUENCE ON KNOWLEDGE AND DENTAL ORAL HEALTH STATUS IN ELEMENTARY GRADERS - Reca Reca; Rosmawati Rosmawati; Ni Ketut Nuratni (FKG Unlam, 2022)
Background: Children at age 10 – 12 is in a period of attention for their dental health. The simplest possible technique for the model to teach tooth brushing is indispensable. Purpose: This study’s purpose is to analyse Dental Health Education influence on the knowledge and Oral Health Index Simplified (OHIS) status of children in elementary school. Method: This study utilized quasi-experimental research. The purposive sampling was used to determine students as much as 60 became the subject of this research and divided every 30 students into an intervention group from SDN 33 and a control group (SDN 3) in the Banda Aceh city. Paired sample and independent t-test were used to analyse the quantitative data results. Results: The result of the mean value of knowledge and dental and oral hygiene status (OHIS status) of students in the pre-test in the intervention group and the control group shows p more than 0. 05. But there is a change in the mean value of knowledge and OHIS status after dental health education (DHE) was carried out in the intervention group (SDN 33) which is statistically significant (p<0.05). Meanwhile, in the control group, the p-value for OHIS status is p>0.05. There are also differences in knowledge and OHIS status of the intervention group compared to the control group, shown by a p-value of less than 0.05. Conclusion: Better change in knowledge and OHIS status prevailed after performing DHE for the elementary grades. Keywords: Dental Health Education (DHE), Elementary, Knowledge, OHIS